Clinical evaluation in adult human revealed the biosimilarity of recombinant Erythropoietin GBPD002 with Eprex® - Mahtab, Mamun Al; Bachar, Sitesh Chandra; Nag, Kakon; Mohiuddin, Mohammad; Rahim, Md. Abdur; Uddin, Md. Helal; Kumar, Samir; Khan, Md. Maksudur Rahman; Sarker, Md. Enamul Haq; Roy, Rony; et al. (Archives of Clinical and Biomedical Research, 2023)
The biosimilarity for erythropoietin (EPO) functionality of GBPD002 (test candidate) and Eprex® (comparator) has been evaluated by comparing the pharmacokinetic (PK) and pharmacodynamic (PD) properties following subcutaneous injection. This was a randomized, double-blinded, twosequence, crossover clinical trial. Subjects were randomly assigned and received a dose (4,000 IU) of either the test or comparator EPO, and received the alternative formulations after 4-weeks of washout period. The PK parameters, viz., maximum observed concentration (Cmax) and area under the curve extrapolated to infinity (AUC0-inf), were calculated with the serum EPO concentrations from blood samples and were found comparable for both formulations. The geometric mean ratios (at 90% CI) of the Cmax and AUCinf were 0.89 and 1.16, respectively, which were within the regulatory range of 0.80 – 1.25. The time-matched serum EPO concentrations and PD markers (reticulocyte, hematocrit, hemoglobin, and red blood cell) denoted a counter-clockwise hysteresis, suggesting a time delay between the observed concentration and the response. ANOVAderived p-value (>0.05) for the effectors clearly revealed the similarity between effects on PD markers for the test and comparator drugs. Both formulations were found tolerated well, and anti-drug antibodies were not observed. Thus, the two formulations are projected to be used interchangeably in clinical settings.